Understanding semantic accents in Japanese–English bilinguals: A feature-based approach. Issue 1 (13th January 2021) - Matsuki, Eriko; Hino, Yasushi; Jared, Debra
Abstract: A bilingual exhibits a "semantic accent" when they comprehend or use a word in one language in a way that is influenced by its translation. Semantic accents are well-captured by feature-based models: however, few studies have specifically examined the processing of features that contribute to a semantic accent. Japanese–English bilinguals and monolinguals of each language completed three feature-based tasks focusing on culture-specific semantic features. Bilinguals exhibited semantic accents in L1 and L2 in that they had stronger associations than monolinguals between the features specific to one culture and words in the other language. Within bilinguals, culture-specific features were more strongly associated with the congruent language than the incongruent language. Finally, changes in the strengths of associations between culture-specific features and words depended more on L2 cultural immersion than L2 proficiency. Semantic accents lessened in L2 and increased in L1 after many years of exposure to the L2 culture.